Cardiovascular Disease Risk after COVID-19 in Diabetic and Non-Diabetic Adults: A Study in Iraq : Risiko Penyakit Kardiovaskular Pasca COVID-19 pada Orang Dewasa Penderita Diabetes dan Non-Diabetes: Sebuah Studi di Irak - Hussein Jaber Hamza (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: COVID-19 has emerged as a global health crisis with significant implications for patients with underlying cardiovascular conditions. Specific Background: Increasing evidence indicates that cardiovascular disease is associated with severe outcomes and complications in infected individuals. Knowledge Gap: Despite numerous studies, there remains a need to synthesize findings on cardiovascular risks and outcomes in diverse populations. Aims: This study aims to analyze the relationship between COVID-19 and cardiovascular disease, focusing on risk factors, clinical manifestations, and outcomes. Results: The findings indicate that patients with pre-existing cardiovascular conditions are more likely to experience severe disease, higher mortality, and long-term complications. Novelty: The study consolidates evidence from multiple studies to provide a comprehensive overview of cardiovascular risks in COVID-19 patients. Implications: These findings support the need for targeted clinical management and preventive strategies for vulnerable populations, contributing to improved healthcare planning and patient care. Keywords: Covid-19, Cardiovascular Disease, Clinical Outcomes, Risk Factors, Mortality Key Findings Highlights Pre-existing conditions are associated with severe cases and complications Multiple studies report elevated mortality among affected patient groups Long-term health issues remain a significant concern after infection